Intrinsic viscosity of aqueous solutions of carboxymethyl guar in the presence and in the absence of salt - Badiger, Manohar V.; Gupta, Nivika R.; Eckelt, John; Wolf, Bernhard A. (Macromolecular Chemistry and Physics, 2008)
Intrinsic viscosities were determined for solutions of CMG in pure water and 0.9 wt.-% aqueous NaCl. To avoid the 0/0-type extrapolation typical for Huggins plots, a new procedure was used. For CMG and pure water, this requires only two adjustable parameters: the specific hydrodynamic volume of the polymer in the limit of infinite dilution and a hydrodynamic interaction parameter. The intrinsic viscosity of CMG (no salt) at room temperature is 6 050 mL . g(-1); approximately half as large as that of Na-PSS of comparable molar mass. The ratio of the intrinsic viscosities with and without salt is approximate to 7 for CMG, as compared to >100 for Na-PSS. The reasons 1:5 5 for the different behaviors of the two types of polyelectrolytes are being discussed.
Keywords: Biopolymers; Carboxymethyl guar; intrinsic viscosity; polyelectrolyte; salt-free solutions

Insight Into the Influence of Salinity on Flow and Flocculation Behavior of Acrylamide-Based Cationic Polyelectrolyte - Ranganath, Suresha P.; Kurian, Rachna; Torris, Arun; Khairnar, Ajay; Ravindranathan, Sapna; Rajamohanan, P. R.; Badiger, Manohar V.; Wolf, Bernhard A. (Journal of Applied Polymer Science, 2026)
The viscometric behavior of aqueous solutions of acrylamide and acrylamidopropyl trimethylammonium chloride copolymers (AM-co-APTMAC) with varying cationic content under different salinity conditions was studied. Viscometric measurements were employed to determine intrinsic viscosity and quantify the influence of electrostatic interactions on chain conformation. Rheology experiments were performed to probe dynamic flow behavior under shear to obtain insights into polyelectrolyte viscoelastic properties under conditions mimicking industrial processes. Viscometric and rheology data analysis is augmented with insights from NMR relaxation and pulsed field gradient NMR diffusion experiments. Further, flocculation of kaolin suspensions was studied using aqueous solutions of AM-co-APTMAC copolymers with different charge fractions in the presence and absence of salt. The physicochemical insights on the behavior of AM-co-APTMAC polyelectrolytes in solution from this study could be relevant in practical applications, such as plants that use seawater or in cases where the ionic strength of suspensions is high due to salinity in the medium.
Keywords: copolymers; polyelectrolytes; structure property relationships; theory and modeling